2001
DOI: 10.1179/026708301101509368
|View full text |Cite
|
Sign up to set email alerts
|

Insitu transmission electron microscopy investigation of crack propagation in single crystal Ni3Al

Abstract: The initiation and propagation of a crack has been investigated in a (1 6 10) [110] oriented Ni 3 Al alloy single crystal by in situ TEM and using tension deformation at room temperature. The result has shown that the macropropagating direction of the crack was parallel to the tensile axis and the crack followed a zigzag path. Trace analysis indicated that the slip on (11 6 1) and ( 111) were activated during the crack propagating process. Calculations show that for this orientation of Ni 3 Al crystal, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Accompanying the deflection of the crack tip, the crack surfaces display a zigzag morphology. The zigzag manner of crack propagation has been observed in metallic thin films of Mo, Ni 3 Ge and Ni 3 Al by transmission electron microscopy [16][17][18], and has been unambiguously ascribed to the alternation of primary and secondary slip systems. This alternation of dislocation slip systems reduces the film thickness intermittently and in turn produces the zigzag crack path [16].…”
mentioning
confidence: 93%
“…Accompanying the deflection of the crack tip, the crack surfaces display a zigzag morphology. The zigzag manner of crack propagation has been observed in metallic thin films of Mo, Ni 3 Ge and Ni 3 Al by transmission electron microscopy [16][17][18], and has been unambiguously ascribed to the alternation of primary and secondary slip systems. This alternation of dislocation slip systems reduces the film thickness intermittently and in turn produces the zigzag crack path [16].…”
mentioning
confidence: 93%
“…The deformation behavior of c 0 -Ni 3 Al can partially reflect the mechanical properties of Ni-based superalloys. At present, some experimental researches [13,14] about crack propagation in c 0 -Ni 3 Al were reported. Re is a critical element for the remarkable improvement of mechanical properties of superalloys [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Superlattice stacking fault formation and twinning during creep in nickel-based superalloy were reported experimentally by Knowles and Chen, [14] and it was found that the formation of high temperature twinning could always be associated with the super extrinsic stacking fault (SESF). Crack propagation in single crystal Ni 3 Al at room temperature was also studied experimentally, [15,16] and the results showed that the room temperature failures were highly localized, often knife-edge sharp and nearly parallel to the primary slip plane. However, at low temperatures, the effects of superdislocation formation and twinning in Ni 3 Al on its fracture toughness have not been explained clearly.…”
Section: Introductionmentioning
confidence: 99%